2022
DOI: 10.3389/fcell.2022.792564
|View full text |Cite
|
Sign up to set email alerts
|

ISYNA1: An Immunomodulatory-Related Prognostic Biomarker in Colon Adenocarcinoma and Pan-Cancer

Abstract: Background: Colon adenocarcinoma (COAD) is a common digestive system tumor in the world. However, the role and function of ISYNA1 (inositol-3-phosphate synthase 1) in COAD remain unclear. We aim to explore the role of ISYNA1 in pan-cancer, especially in COAD.Methods: The expression, clinical characteristic, and prognosis of ISYNA1 in pan-cancer were evaluated using the TCGA (the Cancer Genome Atlas), GTEx (the Genotype-Tissue Expression), and CCLE (Cancer Cell Line Encyclopedia). Pathway enrichment analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…On the other hand, ISYNA1 performed as a tumor suppressor in pancreatic cancer [12]. Evidence showed ISYNA1 acts as a protective factor in OC, high ISYNA1 expression predicted better DSS and longer OS time of ovarian cancer patients [14], this result was consistent with our observations. The inconsistent effects of ISYNA1 may be due to the differences between cancers and environments.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…On the other hand, ISYNA1 performed as a tumor suppressor in pancreatic cancer [12]. Evidence showed ISYNA1 acts as a protective factor in OC, high ISYNA1 expression predicted better DSS and longer OS time of ovarian cancer patients [14], this result was consistent with our observations. The inconsistent effects of ISYNA1 may be due to the differences between cancers and environments.…”
Section: Discussionsupporting
confidence: 91%
“…Current studies indicated that ISYNA1 may act either as an oncogene or tumor suppressor, depending on context. For example, in colon adenocarcinoma, ISYNA1 is a oncogene and a prognostic marker [14]. Overexpression of ISYNA1 promotes the proliferation and inhibits the apoptosis of bladder cancer cells [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that high expression of DTYMK in HCC is associated with poor prognosis, and HCC cell lines with elevated DTYMK expression showed increased sensitivity to multiple chemotherapy agents such as sorafenib [ 50 ]. Conversely, in colon cancer, high expression of ISYNA1 has been linked to poor prognosis and resistance to most anticancer chemotherapy drugs [ 51 ]. Our findings align with those of Guo et al's study [ 50 ].…”
Section: Discussionmentioning
confidence: 99%